The applicability of English language teaching methods to other subjects - Parwiz Hussain (Educational Role of Language Journal, 2020)
This paper reports the findings of a pilot teacher training course being delivered to teachers and teacher educators of Islamic studies subject at British Council Afghanistan. The main aim of the training course was to find out to what extent the methodologies and approaches being used to teach English language are applicable in teaching other subjects. In this research fifteen teachers and educators participated in a four-day training course. The findings show that Test-Teach-Test, Task-based Learning, Jigsaw Reading, and many other teaching methods are easily applicable in teaching Islamic studies.